Development of rogowski coil sensor for partial discharge detection. (August 2019) - Waldi, E P; Frenzi, A Y; Fernandez, R; Darmawan; Darwison; Laksono, H D; Aulia; Hazmi, A; Andre, A; Abral, H; Arief, S; Nawawi, Z; et al.
Abstract: This paper presents the development of Rogowski coil to detect the partial discharge. Rogowski coil sensor is composed of a ferrite core with a various number of turns which is 5, 10, 20 and 30 turns with a half circle and full circle configuration. The sensors need to be tested based on the number of the turns they have in reading the partial discharge signals. The sensor is connected to a digital measurement device such as a digital oscilloscope which has an input impedance of 50 ohms and 1 Mohm with a time frame duration greater than or equal to 20 ms. The reading comparison is not only between the proposed sensors but also with a commercial partial discharge sensor. The partial discharge signal is generated by a commercial charge calibrator. The measurement result shows that using low impedance lead to decreased noise but the reading is too small compared with using high impedance.